Efektivitas Penerapan Kontrak Mudharabah dalam pembiayaan Usaha Mikro pada Bank Syariah - Maritza Tauhid, Datuh; Adawiyah, Rabiatul; Putri Paradibah, Amuria; Rahman, Yulia; Arsyad, Kamaruddin (Kartika: Jurnal Studi Keislaman, 2025)
This study aims to analyze the effectiveness of implementing the mudharabah contract in micro-enterprise financing by Islamic banks in Indonesia. Mudharabah is a profit-sharing contract that theoretically represents an ideal instrument in the Islamic financial system, as it emphasizes justice, cooperation, and risk-sharing. However, in practice, mudharabah financing remains less dominant compared to murabahah-based financing. This study employs a qualitative descriptive method using a literature review approach, drawing from various scientific articles published in the last five years and reference books published in the last ten years. The findings indicate that although mudharabah holds significant potential in empowering micro-enterprises, its implementation still faces several challenges, including low Islamic financial literacy, regulatory and incentive frameworks that are not yet supportive, a transactional business culture, limited monitoring and assistance capacity, and high financing risk. Additionally, the dominance of murabahah-based financing reflects that Islamic banks have not fully utilized the potential of mudharabah as a superior financing instrument to promote Islamic financial inclusion. Recommended strategies include strengthening Islamic financial literacy, utilizing digital technology, and developing community-based mudharabah products. Through synergy among stakeholders, mudharabah has great potential to become a key instrument in strengthening micro-enterprise inclusively and sustainably within the Islamic economic framework.